Behaviour of Concrete-filled Double-skin Short Columns Under Compression Through Finite Element Modelling: SHS Outer and SHS Inner Tubes. (June 2018) - Hassanein, M.F.; Elchalakani, M.; Karrech, A.; Patel, V.I.; Yang, Bo
Abstract: Concrete-filled double-skin tubular (CFDST) columns are formed by sandwiching concrete between two concentric hollow steel tubes. The result is a composite column with the benefits of both steel and concrete properties. When compared to a traditional concrete-filled steel tube (consisting of a single hollow steel tube instead of two), CFDST column is found to have greater axial, flexural and torsional strengths as well as improved strength-to-weight ratios. However, developments in CFDST column configurations can be made by altering the cross-section shape of the steel tubes, which is generally formed from square and circular ones. This paper considers the square CFDST short columns with inner square hollow sections (i.e. SHS outer and SHS inner tubes). This is because; in additional to their advantages shown above, they were seldom considered in literature especially by virtual testing. Accordingly, this paper is devoted for the finite element (FE) modelling of this type of composite columns by using ABAQUS program. Innovatively, this paper, rather than different investigations in literature, uses the most accurate constitutive models of both the cold-formed steel (i.e. Ramberg-Osgood model) and the confined concrete infill in double-skin tubes. Prior to parametric studies, the program has been validated using previous experimental results to ensure that the chosen combination of the materials could provide accurate and reliable results for the proposed models. The paper is then extends through parametric studies to investigate the effects of the key parameters affecting the general behaviour of this column under axial compressive loading, which exceeds the range of materials currently available in the available experiments. The paper additionally explores the effect of the eccentric loads on the behaviour of such columns, rarely done in literature, and comparisons with available theoretical moment-interaction curves have been considered. Overall, this paper provides new results that might aid in widening the practical usage of such column.